Tinjauan Penyebab Peserta Non Aktif Bpjs di Puskesmas Kecamatan Cengkareng - Navry Nanda Aprilian; Deasy Rosmala Dewi; Puteri Fannya; Daniel Happy Putra (Jurnal Siti Rufaidah, 2024)
Abstract: The Social Security Administering Body (BPJS) is an organizing body whose membership is mandatory. Every company is required to register its workers for a minimum of 6 months, while those who do not work for a company are required to register themselves and their family members with BPJS. Each BPJS participant will be charged a contribution, the amount of which will be determined later. Inactive BPJS membership is a participant whose registration process is hampered and services become payable independently. The aim of the research is to review the causes of Non-active BPJS participants in Cengkareng sub-district. The research method is a quantitative approach. The technique uses saturated sample observations. The research results showed that there were 75 Non-active participants. Of the 75 samples, there were 34 participants who were inactive due to premiums (45.33%), 13 participants because they left of their own accord (17.33%), 7 participants because their children were PPU> 21 years (9.33%), 10 participants were not covered (13 .33%), 11 participants with double data (14.66%). Follow-up of Inactive BPJS membership at the Cengkareng Community Health Center, there were 65 participants (86.67%) taking care of returning BPJS participants and 10 participants (13.33%) continuing at their own expense. Of the number of BPJS participants who registered for treatment at the Cengkareng sub-district health center, their membership status was inactive due to premiums being one of the highest. The follow-up is to pay all arrears and take care of returning the membership to the nearest BPJS. Suggestions In accordance with the vision and mission of BPJS Health to be able to improve the quality of service to participants, BPJS Health must be able to improve the quality of service, especially in the field of information technology which can be made to remind BPJS Health participants, especially those whose membership status is inactive, by using E-mail and Whatsapp.